Seasonal Home Advantage in English Professional Football; 1973-2018 - Thomas Peeters; Jan C. van Ours (Tinbergen Institute, 2020)
We analyze 45 years of data from English professional football focusing on the determinants of home advantage. We conclude that seasonal home advantage is substantial and positively related to within-team variation in attendance. Furthermore, despite big cross-league differences in attendance, the average home advantage is about the same across the English leagues. The average home advantage over the period of analysis was 0.63 points and 0.45 goals difference. Finally, we find that over time there is a substantial decline in the home advantage that materializes equally across the leagues.
Keywords: L83; Z21; 330; Professional football; home advantage; managers